Total antioxidant activity in Quercus ilex resprouts after fire - El Omari, Bouchra; Fleck, Isabel; Aranda, Xavier; Abadía, Anunciación; Cano, Antonio; Arnao, Marino B. (Plant Physiology and Biochemistry, 2003)
After ﬁre, holm oak (Quercus ilex L.) resprouts have a higher light availability and photosynthetic activity than control plants in intact vegetation. To assess the differences in protection between these plants, we determined, in two forests, changes in gas-exchange rates, chlorophyll ﬂuorescence parameters, chloroplast pigment content and total antioxidant activity (TAA) in different seasons, at different times of the day and in relation to leaf age. The end-point method used for TAA determination allowed the evaluation of the relative contribution of hydrophilic and lipophilic antioxidants in leaf extracts. High correlations were obtained between lipophilic TAA and certain chloroplast pigment content, the highest contribution being provided by b-carotene and the components of the xanthophyll cycle (zeaxanthin + antheraxanthin, violaxanthin). All leaves showed a much higher contribution (94–99%) of hydrophilic than lipophilic antioxidants to TAA. In summer, at midday, photosynthetic rates and TAA were higher in resprouts. In these plants, reduced xanthophyll-cycle participation (as shown by non-photochemical quenching (NPQ) and xanthophyll pool content) was compensated by an increased participation of hydrophilic antioxidants. No effect of time of day or plant age was observed. The results suggest that energy dissipation as heat, and detoxiﬁcation mechanisms contribute to the protective strategies of control plants and resprouts, albeit to a different extent.
Keywords: carotenoids; non-photochemical quenching; Quercus ilex; reactive oxygen species; Resprouts; total antioxidant activity

Total antioxidant activity in Quercus ilex resprouts after fire - El Omari, Bouchra; Fleck, Isabel; Aranda, Xavier; Abadía, Anunciación; Cano, Antonio; Arnao, Marino B (Plant Physiology and Biochemistry, 2003)
After ﬁre, holm oak (Quercus ilex L.) resprouts have a higher light availability and photosynthetic activity than control plants in intact vegetation. To assess the differences in protection between these plants, we determined, in two forests, changes in gas-exchange rates, chlorophyll ﬂuorescence parameters, chloroplast pigment content and total antioxidant activity (TAA) in different seasons, at different times of the day and in relation to leaf age. The end-point method used for TAA determination allowed the evaluation of the relative contribution of hydrophilic and lipophilic antioxidants in leaf extracts. High correlations were obtained between lipophilic TAA and certain chloroplast pigment content, the highest contribution being provided by b-carotene and the components of the xanthophyll cycle (zeaxanthin + antheraxanthin, violaxanthin). All leaves showed a much higher contribution (94–99%) of hydrophilic than lipophilic antioxidants to TAA. In summer, at midday, photosynthetic rates and TAA were higher in resprouts. In these plants, reduced xanthophyll-cycle participation (as shown by non-photochemical quenching (NPQ) and xanthophyll pool content) was compensated by an increased participation of hydrophilic antioxidants. No effect of time of day or plant age was observed. The results suggest that energy dissipation as heat, and detoxiﬁcation mechanisms contribute to the protective strategies of control plants and resprouts, albeit to a different extent.
Keywords: carotenoids; non-photochemical quenching; Quercus ilex; reactive oxygen species; Resprouts; total antioxidant activity

Characterization of the responses of cork oak (Quercus suber) to iron deficiency - Gogorcena, Yolanda; Molias, Nuria; Larbi, Ajmi; Abadía, Javier; Abadía, Anunciación (Tree Physiology, 2001)
We studied responses of cork oak (Quercus suber L.) to iron (Fe) deficiency by comparing seedlings grown hydroponically in nutrient solution with and without Fe. Seedlings grown without Fe developed some responses typical of the Strategy I group of Fe-efficient plants, including two- and fourfold increases in plasma membrane ferric chelate reductase activity of root tips after 2 and 4 weeks of culture in the absence of Fe, respectively. Moreover, seedlings grown hydroponically for 2 weeks without Fe caused marked decreases in the pH of the nutrient solution, indicating that root plasma membrane ATPase activity was induced by Fe deficiency. Iron deficiency also caused marked decreases in leaf chlorophyll and carotenoid concentrations, and chlorophyll concentrations were decreased more than carotenoid concentrations. Iron deficiency resulted in an 8% decrease in the dark-adapted efficiency of photosystem II and a 43% decrease in efficiency of photosystem II at steady-state photosynthesis. No major root morphological changes were observed in seedlings grown without Fe, although seedlings grown in Fe-deficient nutrient solution had light-colored roots in contrast to the dark brown color of control roots.
10.1093/treephys/21.18.1335
Keywords: Fe deficiency; ferric chelate reductase; plant nutrition; rhizosphere acidification.

Characterization of the responses of cork oak (Quercus suber) to iron deficiency - Gogorcena, Yolanda; Molias, Nuria; Larbi, Ajmi; Abadía, Javier; Abadía, Anunciación (Tree Physiology, 2001)
We studied responses of cork oak (Quercus suber L.) to iron (Fe) deficiency by comparing seedlings grown hydroponically in nutrient solution with and without Fe. Seedlings grown without Fe developed some responses typical of the Strategy I group of Fe-efficient plants, including two- and fourfold increases in plasma membrane ferric chelate reductase activity of root tips after 2 and 4 weeks of culture in the absence of Fe, respectively. Moreover, seedlings grown hydroponically for 2 weeks without Fe caused marked decreases in the pH of the nutrient solution, indicating that root plasma membrane ATPase activity was induced by Fe deficiency. Iron deficiency also caused marked decreases in leaf chlorophyll and carotenoid concentrations, and chlorophyll concentrations were decreased more than carotenoid concentrations. Iron deficiency resulted in an 8% decrease in the dark-adapted efficiency of photosystem II and a 43% decrease in efficiency of photosystem II at steady-state photosynthesis. No major root morphological changes were observed in seedlings grown without Fe, although seedlings grown in Fe-deficient nutrient solution had light-colored roots in contrast to the dark brown color of control roots.
10.1093/treephys/21.18.133510.1093/treephys/21.18.1335
Keywords: Fe deficiency; ferric chelate reductase; plant nutrition; rhizosphere acidification.